Exosome-Mediated Genetic Information Transfer, a Missing Piece of Osteoblast–Osteoclast Communication Puzzle - Yin, Pengbin; Lv, Houchen; Li, Yi; Deng, Yuan; Zhang, Licheng; Tang, Peifu (Frontiers in Endocrinology, 2017)
The skeletal system functions and maintains itself based on communication between cells of diverse origins, especially between osteoblasts (OB) and osteoclasts (OC), accounting for bone formation and resorption respectively. Previously, protein-level information exchange has been the research focus and this has been discussed in detail. The regulative effects of microRNAs on OB and OC ignite the question as to whether genetic information could be transferred between bone cells. Exosomes, extracellular membrane vesicles 30–100 nm in diameter, have recently been demonstrated to transfer functional proteins, mRNAs and miRNAs, and serve as mediators of intercellular communication. By reviewing the distinguishing features of exosomes, a hypothesis was formulated and evaluated in this article that exosome-mediated genetic information transfer may represent a novel strategy for osteoblast-osteoclast communication. The exosomes may coordinately regulate these two cells under certain physiological conditions by transferring genetic information. Further research in exosome-shuttered microRNAs in OB-OC communication may add a missing piece to the bone cells communication “puzzle”.